Across-Sectional Observational Study on Drug Utilization and Prescribing Patterns of Antibiotics in Lower Respiratory Tract Infections in Tertiary Care Teaching Hospital (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Lower respiratory tract infections (LRTIs) affect the airways and lungs, including conditions such asbronchitis, bronchiolitis, and pneumonia. These infections are a leading cause of mortality from infectious diseasesworldwide, often caused by bacterial and viral pathogens. Despite their prevalence, antibiotic prescribing trends inLRTIs remain underexplored, particularly in Indian healthcare settings. Objectives: This study investigates the patternsof antibiotic prescription for LRTIs, including bronchitis, in a tertiary care teaching hospital, with a focus on monoandpoly-antibiotic therapies. Methods: A cross-sectional observational study was conducted at Sri VenkateswaraInstitute of Medical Science, Tirupathi, India. Data were collected from 72 participants, including demographicinformation, clinical history, and self-medication practices. Statistical analysis was performed using the StatisticalPackage for Social Sciences software. The study focused on prescription patterns, gender distribution, and the typesof antibiotics prescribed. Results: A greater proportion of males than females were found to suffer from LRTIs. Outof the total prescriptions analyzed, 57% were for mono-antibiotic therapy, while 7% involved poly-antibiotic therapy.LRTI diagnoses, including non-specific LRTI, pneumonia, tuberculosis, and pleural effusion, accounted for 76.28% ofthe cases, with 23.6% of the cases attributed to bronchitis. Augmentin and doxycycline were the two most frequentlyprescribed antibiotics. A comparison of the prescribed daily dose and defined daily dose of antibiotics was performed.Conclusions: The study highlights the predominant use of mono-antibiotic therapy over poly-antibiotic therapy intreating LRTIs. The findings underscore the need for better antibiotic stewardship to manage the rising number ofLRTI patients. Further efforts are required to optimize treatment strategies and reduce the risk of antibiotic resistance.